2007
DOI: 10.1002/pds.1417
|View full text |Cite
|
Sign up to set email alerts
|

Use of anxiolytic or hypnotic drugs and total mortality in a general middle‐aged population

Abstract: PurposeThe aim of the study was to evaluate the effect of the consumption of anxiolytic or hypnotic drugs on total mortality in a general population.MethodsWe followed a cohort of 7225 men and 7726 women aged 40–42 years who underwent health surveys in 1985–1989 in two Norwegian counties, with respect to deaths. Mean follow‐up period was 18 years. The subjects were categorised according to frequency of anxiolytic or hypnotic drug use during the last month: daily, every week, less than every week and not used d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 83 publications
(132 reference statements)
3
47
2
2
Order By: Relevance
“…Previous studies have been inconsistent, with some studies observing significant relationships between hypnotic prescriptions and mortality [16,[20][21][22][23][24][25]37] and others not [16][17][18][19]. Our findings suggest that these differences are probably largely due to failure to take into account confounding associations, notably common affective symptoms and sleep complaints, although other factors such as study design, participant age, and class of hypnotics probably also influence study outcome.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Previous studies have been inconsistent, with some studies observing significant relationships between hypnotic prescriptions and mortality [16,[20][21][22][23][24][25]37] and others not [16][17][18][19]. Our findings suggest that these differences are probably largely due to failure to take into account confounding associations, notably common affective symptoms and sleep complaints, although other factors such as study design, participant age, and class of hypnotics probably also influence study outcome.…”
Section: Discussioncontrasting
confidence: 48%
“…Four observational studies in young adults [16,17] and elderly people [18,19] found no significant associations between hypnotics and all-cause mortality. Other studies reported a significant association with excessive all-cause deaths in adults [20][21][22]. Two large studies with very wide age ranges from young adult to older elderly people [23][24][25] found significant associations in all age groups, including the elderly.…”
Section: Introductionmentioning
confidence: 95%
“…Several reports carefully examined insomnia and depression as potential confounders of the association of hypnotics with mortality, finding that insomnia and depression could explain little if any of this association 19,[22][23][24] . Note also that the evidence does not permit us to assume that causality between insomnia, depression, and hypnotic usage is a one-way path when contemplating confounder control, as there is reverse causality 25,26 .…”
Section: Results Had Many Similarities To Those Of Weich Et Almentioning
confidence: 99%
“…In combined clinical trials, participants randomized to hypnotics suffered 2.1 times as many incident (new) depressions as those randomized to placebo (P<0.002) 25 . These were not exacerbations of pre-existing depressions.…”
Section: Hypnotics Increase Incidence Of Clinical Depressionmentioning
confidence: 99%
“…All men (15 606) and women (14 748) aged 40-42 in the two Norwegian counties of Østfold and Aust-Agder were invited to participate in a population-based health survey organised by the National Health Screening Service, and has been described earlier [12][13][14] . The health survey was directed toward cardiovascular disease.…”
Section: Health Surveys-information On Independent Variablesmentioning
confidence: 99%